2000
DOI: 10.1073/pnas.100101997
|View full text |Cite
|
Sign up to set email alerts
|

A ligand-reversible dimerization system for controlling protein–protein interactions

Abstract: Chemically induced dimerization provides a general way to gain control over intracellular processes. Typically, FK506-binding protein (FKBP) domains are fused to a signaling domain of interest, allowing crosslinking to be initiated by addition of a bivalent FKBP ligand. In the course of protein engineering studies on human FKBP, we discovered that a single point mutation in the ligandbinding site (Phe-36 3 Met) converts the normally monomeric protein into a ligand-reversible dimer. Two-hybrid, gel filtration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
140
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(146 citation statements)
references
References 26 publications
4
140
0
Order By: Relevance
“…Chimeric MA proteins that can be induced to dimerize were created by fusion of MA with the FK506-binding protein (FKBP) (60)(61)(62) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Chimeric MA proteins that can be induced to dimerize were created by fusion of MA with the FK506-binding protein (FKBP) (60)(61)(62) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Clackson et al developed a nonnative receptor ligand pair, using the "bump-hole" approach. A FKBP12(F36V) mutant selectively binds a "bumped" SLF analog, also referred to as SLF', with very high affinity (K D ¼ 0.094 nM) [26]. In 2009 Robers et al reported optimized SLF' fluorophore conjugates, validated by morphology analysis using a number of FKBP(F36V) fusion proteins in live cell imaging [27].…”
Section: Noncovalent Protein Tagsmentioning
confidence: 99%
“…We have exploited a conditional aggregation domain (CAD) system (Rollins et al, 2000), which was initially used to allow regulated protein secretion in mammalian cells . This system uses multiple domains of the FK506 binding protein engineered to aggregate in the absence of a synthetic ligand.…”
mentioning
confidence: 99%